2019
DOI: 10.1002/mgg3.750
|View full text |Cite
|
Sign up to set email alerts
|

Copy number alterations associated with clinical features in an underrepresented population with breast cancer

Abstract: Background As the most incident tumor among women worldwide, breast cancer is a heterogeneous disease. Tremendous efforts have been made to understand how tumor characteristics as histological type, molecular subtype, and tumor microenvironment collectively influence disease diagnosis to treatment, which impact outcomes. Differences between populations and environmental and cultural factors have impacts on the origin and evolution of the disease, as well as the therapeutic challenges that arise du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Previous systematic studies on mammalian transcriptomes have suggested that more than 70% of the genome undergoes transcription, and that most of these transcripts are weakly expressed non-coding RNA 30 31. In addition, although mRNA processing is a stringently regulated mechanism that enables the generation of multiple functional variants of an individual gene, many of these mechanisms are highly perturbed and can be seized to favour the malignant state of tumours 14–20. As the RNA sequence quality was reliable in our study, it is reasonable to interpret the intronic and intergenic transcriptions as true reads.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Previous systematic studies on mammalian transcriptomes have suggested that more than 70% of the genome undergoes transcription, and that most of these transcripts are weakly expressed non-coding RNA 30 31. In addition, although mRNA processing is a stringently regulated mechanism that enables the generation of multiple functional variants of an individual gene, many of these mechanisms are highly perturbed and can be seized to favour the malignant state of tumours 14–20. As the RNA sequence quality was reliable in our study, it is reasonable to interpret the intronic and intergenic transcriptions as true reads.…”
Section: Discussionmentioning
confidence: 75%
“…These processes are influenced both by genetic factors and environmental factors, for example, immune responses,34 35 age,36 heat stress37 and DNA damage 38. CNAs have also been described as having a particular association with AS 16 19. In this study, we identified previously known tumour-specific AS in cancer driver genes involved in disease pathogenesis (e.g., HRAS , MDM2 , FGFR2 and VEGFA ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Breast cancer is a also heterogeneous disease. The individual's genetic in combination with histological types of tumors, molecular subtypes, and tumor microenvironment contribute to the development of the disease [3].…”
Section: Introductionmentioning
confidence: 99%